AI-Enabled Digital Marketing Training for Economic Empowerment in an Orphaned Islamic Boarding School - Heru Kustanto; Pipit Rosita Andarsari; Yuniar Fitriyani (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community service aimed to enhance the economic independence of students and caregivers at Pondok Pesantren Yatim Dhuafa (PPYD) Al Ikhlas (Al Ikhlas Orphaned and Poor Islamic Boarding School) through artificial intelligence (AI)-based digital marketing training. The primary problem was low digital literacy and reliance on conventional marketing methods, which limited product reach. Method: A participatory action research (PAR) approach was employed. Activities included conceptual training, brand identity workshops, hands-on practice with AI tools (ChatGPT, Canva AI), and joint formulation of a digital marketing roadmap. The program involved 35 participants and was conducted over 4.5 hours. Practical Applications: The service directly improved participants' digital marketing competencies, optimized four business social media accounts, and increased posting frequency by 475% within two weeks post-intervention. AI integration enabled more efficient and creative promotional content production. Conclusion: The program succeeded in increasing participants' understanding by 68% (post-test mean score 82.4), forming a Digital Pesantren Team, and strengthening entrepreneurial motivation. A structured three-phase sustainability plan has been developed to maintain long-term impact.